Modulating AMPA receptor-dependent synaptic plasticity: Mechanistic interventions against remifentanil-induced hyperalgesia in reoperative rats – A randomised controlled trial - Suqian Guo; Qi Zhao; Linlin Zhang; Chengcheng Song; Guolin Wang (Indian Journal of Anaesthesia)
Background and Aims: Intraoperative remifentanil can induce postoperative hyperalgesia. In clinical practice, either unplanned or planned second operations may occur within a short period. However, the impact of remifentanil during this process remains unclear. This study aimed to investigate the pain threshold following two incisional operations under remifentanil analgesia and to examine the contribution of the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR). Methods: Experimental rats received remifentanil infusion combined with plantar incision. This dual intervention was repeated twice, separated by a 7-day interval. After completing both treatment cycles, mechanical paw withdrawal thresholds (PWTs) and thermal withdrawal latencies (PWLs) were assessed. Simultaneously, C-fibre evoked field potentials were recorded in parallel with dendritic spine morphology analysis. Additionally, the intrathecal administration of 1-naphthylacetyl spermine trihydrochloride (NASPM) was used to investigate the role of the AMPAR. Results: In rats with two incisions and remifentanil infusions, the second treatment led to lower minimum PWT and PWL values than the first. Compared to controls, these rats exhibited a significantly greater increase in the C-fibre-evoked field potential, as well as in the number of primary branches and spines of spinal dorsal horn neurons. The AMPAR inhibitor NASPM attenuated remifentanil-induced exacerbation of reoperative hyperalgesia, reversed remifentanil-enhanced spinal long-term potentiation, and mitigated the associated morphological changes. Conclusion: Repetitive remifentanil administration during consecutive operations within a short temporal window significantly potentiated opioid-induced hyperalgesia in a rat reoperation model. This hyperalgesic priming was mechanistically associated with upregulated trafficking of spinal AMPARs.